CSIG-24. GABP LINKS AMPK SIGNALING TO TERT REGULATION IN A TERT PROMOTER MUTATION DEPENDENT MANNER. (11th November 2019) - McKinney, Andrew; Amen, Alexandra; Stevers, Nicholas; Costello, Joseph
Abstract: Over 90% of human tumors achieve immortality by reactivating telomerase reverse transcriptase ( TERT ), the catalytic subunit of telomerase. Two mutually exclusive, heterozygous mutations that activate the TERT promoter ( TERT p) occur in a wide range of cancers including 80% of glioblastomas (GBM). The mutations and TERT p activation enable cells to avoid replicative senescence and continue to divide beyond the normal limits on cellular lifespan, thus becoming immortal. Our lab has demonstrated that each mutation creates a novel E26-transformation specific binding site that allows the tetrameric form of the GA-binding protein GABP to bind and aberrantly activate the mutant TERT p. We further showed that reducing a tetramer-forming subunit of GABP, the GABPB1L transactivating subunit, reverses cellular immortality in vitro and reduces tumor growth in vivo . Beyond GABP, little is known about pathways that contribute to immortality via activation of the mutant TERT p. The heterotrimeric 5' AMP-activated protein kinase (AMPK) complex is activated in human GBM compared to normal brain, and was previously implicated in regulating GABP expression. Here, we have determined that AMPK inhibition decreases transcription of both subunits of the tetrameric GABP complex ( GABPA and GABPB1L ) in GBM cells, and is sufficient to reduce TERT expression and telomerase activity in a TERT promoter mutation dependent manner. Together, these data suggest a novel and targetable connection between the AMPK signaling axis, telomerase activity and potentially tumor cell immortality.